Customary Sanctions: Social Control of Rural Development (Jurnal Bina Praja, 2023)
The whole community should be involved in rural development. However, occasionally, some obstacles cause a lack of community participation. Therefore, several aspects, like socio-cultural and customary practices, are utilized for the rural development of indigenous peoples. This study aimed to analyze customary sanctions' function as social control in rural development for the indigenous Pepadun community in Srimenanti Village, Negara Batin sub-districts, Way Kanan Regency. This field research used a descriptive qualitative approach. The primary data were collected from interviews and observations, while the secondary data were assembled from Statistics Indonesia and customary records owned by informants. Transcription and description were conducted for data processing and analysis. As a result, customary sanctions enforced by Members of the Indigenous Council (Anggota Dewan Adat) have an important role in the social control of deviant behavior through agreed Bia (Biaya Adat/Customary Fees). Additionally, customary rules also play a role in filling both physical and non-physical rural development of the skills in the rural government and customary administrators. These customary sanctions run on community participation in complying with agreed customary rules.
Keywords: customary sanctions; social control; rural development; Lampung Pepadun